Long-term effect of transcranial direct current stimulation in the treatment of chronic tinnitus: A randomized, placebo-controlled trial - Mares, Tadeas; Albrecht, Jakub; Buday, Jozef; Podgorna, Gabriela; Le, Thai Hong; Magyarova, Eva; Poshor, Katerina; Halik, Jakub; Buna, Jan; Capek, Vaclav; Kostylkova, Lenka; Klasova, Johana; et al. (Frontiers in Psychiatry, 2022)
Introduction: Tinnitus is an intrusive and chronic illness affecting a significant portion of the population, decreasing affected individuals' quality of life and socioeconomic functioning. Transcranial Direct Current Stimulation (tDCS) is a non-invasive neuromodulatory method utilizing weak electrical currents to elicit short and long-term central nervous system changes. Several studies have proven its effect on tinnitus. We aimed to broaden the knowledge and provide data on the effect and its retention. Methods: In the randomized, double-blinded, sham-controlled trial, 39 patients (active n=19, sham n=20) underwent bifrontal tDCS (anode over right dorsolateral prefrontal cortex (DLPFC), cathode left DLPFC, current of 1.5 mA, 20 minutes, 6 sessions in 2 weeks). Tinnitus Functional Index (TFI), Iowa Tinnitus Handicap Questionnaire (ITHQ), Beck Anxiety Inventory (BAI), Zung Self-Rating Depression Scale (SDS), and WHO-Quality of Life-BREF were employed in 4 evaluation points, including the follow-ups of 6 weeks and six months. Results: We reached a delayed, significant long-term improvement (p<0.05) in auditory difficulties associated with tinnitus and noticed it even after six months compared to placebo. We also reached a short-term, negative effect in the psychological domain of WHO-Quality of Life-BREF (p<0.05). Not all subdomains of TFI and ITHQ reached statistical significance during the data analysis, even though specific positive trends were noticed. Conclusion: We proved partial, positive, long-term effects of tDCS on tinnitus and short-term, negative, transient effect on a specific aspect of the general quality of life. We expanded upon the results of previous trials and provided data concerning the longevity and the precise effect of multiple sessions, bifrontal DLPFC tDCS. Our sample size (n=39) was limited, which might have contributed to the lesser statistical power of the analyzed items. Clinical Trial Registration: www.ClinicalTrials.gov, identifier: NCT05437185